2020
DOI: 10.1371/journal.pone.0235136
|View full text |Cite
|
Sign up to set email alerts
|

αIIbβ3 variants in ten families with autosomal dominant macrothrombocytopenia: Expanding the mutational and clinical spectrum

Abstract: Background Rare pathogenic variants in either the ITGA2B or ITGB3 genes have been linked to autosomal dominant macrothrombocytopenia associated with abnormal platelet production and function, deserving the designation of Glanzmann Thrombasthenia-Like Syndrome (GTLS) or ITGA2B/ITGB3-related thrombocytopenia. Objectives To describe a series of patients with familial macrothrombocytopenia and decreased expression of αIIbβ3 integrin due to defects in the ITGA2B or ITGB3 genes. Methods We reviewed the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Because it is a recessive autosomal disorder, only homozygote subjects exhibit moderate-severe mucocutaneous bleeding starting in childhood, whereas heterozygote individuals tend to be asymptomatic [ 1 , 8 , 163 ]. On the other hand, some ITGA2B and ITGB3 heterozygous variants can cause autosomal dominant inherited thrombocytopenia [ 39 ].…”
Section: Inherited Platelet Disorders Of Particular Clinical Relevancementioning
confidence: 99%
“…Because it is a recessive autosomal disorder, only homozygote subjects exhibit moderate-severe mucocutaneous bleeding starting in childhood, whereas heterozygote individuals tend to be asymptomatic [ 1 , 8 , 163 ]. On the other hand, some ITGA2B and ITGB3 heterozygous variants can cause autosomal dominant inherited thrombocytopenia [ 39 ].…”
Section: Inherited Platelet Disorders Of Particular Clinical Relevancementioning
confidence: 99%
“…Early MK maturation was normal, but proplatelets were short and had enlarged tips. Recently, Morais et al 73 have reported more European cases with AD variants affecting the salt bridge and all with mild forms of MTP; again the authors emphasized the phenotypic variability of such cases and which extended to the degree of spontaneous activation of αIIbβ3.…”
Section: Macrothrombocytopenia (Mtp) and A Gt-like Statementioning
confidence: 99%
“…76 Platelet anisotropy was again associated with enlarged "fused" α-granules. Recently, Morais et al 73 have added p.G976V in αIIb and p.T720P, p.H722P and p.R734H (p.…”
Section: Macrothrombocytopenia (Mtp) and A Gt-like Statementioning
confidence: 99%
See 1 more Smart Citation
“…Surface expression of PLT glycoproteins (GP) was measured by FCM using citrated PB and a direct immunofluorescence technique, as previously described in detail [12]. Monoclonal antibodies (mAbs) used, conjugated with fluorescein isothiocyanate (FITC) or with phycoerythrin (PE) were from Becton Dickinson, San Jose, CA, USA (BD) or from Dako, Glostrup, Denmark (DK): FITC-conjugated anti-CD41a (clone HIP8) (BD, 333147) FITC-conjugated anti-CD61 (GPIIIa) (clone RUU-PL7F12) (BD, 347407), and PE-conjugated anti-CD42b (GPIb) (clone AN51) (DK, R7014).…”
Section: Flow Cytometry Studiesmentioning
confidence: 99%